Quantifying CO 2 Insertion Equilibria for Low-Pressure Propene Oxide and Carbon Dioxide Ring Opening Copolymerization Catalysts - Eisenhardt, KHS; Fiorentini, F; Lindeboom, W; Williams, CK (American Chemical Society, 2024)
While outstanding catalysts are known for the ring-opening copolymerization (ROCOP) of CO2 and propene oxide (PO), few are reported at low CO2 pressure. Here, a new series of Co(III)M(I) heterodinuclear catalysts are compared. The Co(III)K(I) complex shows the best activity (TOF = 1728 h–1) and selectivity (>90% polymer, >99% CO2) and is highly effective at low pressures (<10 bar). CO2 insertion is a prerate determining chemical equilibrium step. At low pressures, the concentration of the active catalyst depends on CO2 pressure; above 12 bar, its concentration is saturated, and rates are independent of pressure, allowing the equilibrium constant to be quantified for the first time (K eq = 1.27 M–1). A unified rate law, applicable under all operating conditions, is presented. As proof of potential, published data for leading literature catalysts are reinterpreted and the CO2 equilibrium constants estimated, showing that this unified rate law applies to other systems.